Stressin(1)-A, a Potent Corticotropin Releasing Factor Receptor 1 (CRF(1))-Selective Peptide Agonist - Rivier, Jean (2007)
The potencies and selectivity of peptide CRF antagonists is increased through structural constraints suggesting that the resulting ligands assume distinct conformations when interacting with CRF(1) and CRF(2) receptors. To develop selective CRF receptor agonists, we have scanned the sequence -Gln-Ala-His-Ser-Asn-Arg- (residues 30–35 of [DPhe(12),Nle(21,38)]Ac-hCRF(4-41)) with an i-(i + 3) bridge consisting of the Glu(i)-Xaa-Xbb-Lys(i+3) scaffold where residues i = 30, 31 and 32. When i = 31 stressin(1)-A, a potent CRF(1) receptor-selective agonist was generated. In vitro, stressin(1)-A was equipotent to h/rCRF to release ACTH. Astressin(1)-A showed a low nanomolar affinity for CRF(1) receptor (K(i) = 1.7 nM) and greater than 100-fold selectivity versus CRF(2) receptor (K(i) = 222 nM). Stressin(1)-A released slightly less ACTH than oCRF in adult adrenal-intact male rats, with increased duration of action. Stressin(1)-A, injected intra-peritoneally, induced pellet output (a CRF(1) receptor-mediated response) and did not influence gastric emptying and blood pressure (CRF(2) receptor-mediated responses).